2017
DOI: 10.1590/1806-9282.63.09.736
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional knowledge and body mass index: A cross-sectional study

Abstract: Objective: To verify the knowledge about food and nutrition and its association with the nutritional status of obese patients with noncommunicable diseases (NCDs), and to identify the relationship between information sources and level of knowledge. Method: Cross-sectional study that included 263 outpatients of a cardiology referral hospital in Porto Alegre, Rio Grande do Sul, Brazil. The participants filled out a questionnaire on socioeconomic data and knowledge about food and nutrition and had their nutrition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 16 publications
2
15
0
4
Order By: Relevance
“…Earlier, a study found that lower levels of physical activity leads to increase risk of excess weight [ 45 ]. Our finding that nutritional KAP scores had an inverse association with BMI was in accord to a previous study, where negative association of nutritional knowledge with BMI has been reported [ 46 ]. Up to our best knowledge, this is the first study, which found an inverse association between nutritional KAP scores and BMI in medical students in China.…”
Section: Discussionsupporting
confidence: 93%
“…Earlier, a study found that lower levels of physical activity leads to increase risk of excess weight [ 45 ]. Our finding that nutritional KAP scores had an inverse association with BMI was in accord to a previous study, where negative association of nutritional knowledge with BMI has been reported [ 46 ]. Up to our best knowledge, this is the first study, which found an inverse association between nutritional KAP scores and BMI in medical students in China.…”
Section: Discussionsupporting
confidence: 93%
“…The BMI also explained the level of the knowledge of nutrition. It is in line with previous reports that indicate that obese mothers have PLOS ONE a lower level of knowledge about healthy eating compared to mothers with normal body weight [58,59].…”
Section: Plos Onesupporting
confidence: 92%
“…Estos resultados son consistentes con estudios similares [22][23][24] . Estos resultados podrían deberse al hecho de que, por cultura, las mujeres se sienten más comprometidas y responsables en cuanto a la compra y la preparación de los alimentos en el hogar 25 . No obstante, otros estudios 9 difieren con nuestros resultados, en los que se ha demostrado que los adolescentes presentaron actitudes desfavorables y prácticas alimentarias inadecuadas.…”
Section: Discussionunclassified